DIÁLOGO ENTRE OS SUBSISTEMAS SOCIAIS DA SAÚDE E DO DIREITO: ATRIBUIÇÕES E LIMITES - Pereira, Wilson Medeiros (Revista da AJURIS - Qualis A2, 2016)
DIALOGUE BETWEEN SOCIAL SUBSYSTEMS OF HEALTH AND THE LAW: RESPONSIBILITIES AND LIMITS RESUMO: Aplicação da teoria dos sistemas de Niklas Luhmann na atuação do subsistema saúde e do subsistema direito. Análise da dispensação de medicamentos essenciais, com enfoque na alteração trazida pela Lei nº 12.401/2011. PALAVRAS-CHAVE: teoria; sistema; direito; saúde. ABSTRACT: Application of the theory of Niklas Luhmann’s systems in the health subsystem performance and the right subsystem. Analysis of dispensing essential medicines, with a focus on changes brought by Law nº 12.401/2011. KEYWORDS: theory; system; right; health. SUMÁRIO: Introdução; 1 Histórico brasileiro do acesso à saúde; 2 O subsistema social do direito; 3 O subsistema social da saúde; 4 Dispensação de medicamentos essenciais antes e depois da Lei nº 12.401/2011; 5 Diálogo entre o sistema da saúde e o subsistema do direito; Considerações finais; Referências. SUMMARY: Introduction; 1 Brazilian access to health records; 2 The social subsystem law; 3 The social subsystem of health; 4 Dispensation of essential drugs before and after the Law nº 12.401/2011; 5 Dialogue between the health system and the subsystem of law; Final considerations; References.